2021
DOI: 10.1016/j.avsg.2020.08.114
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Surgery Practice Guidelines during COVID-19 Pandemic in a Setting of High Work Volume Against Limited Resources: Perspective of a Developing Country

Abstract: Background The situation of coronavirus disease 2019 (COVID-19) pandemic in the Indian subcontinent is worsening. In Bangladesh, rate of new infection has been on the rise despite limited testing facility. Constraint of resources in the health care sector makes the fight against COVID-19 more challenging for a developing country like Bangladesh. Vascular surgeons find themselves in a precarious situation while delivering professional services during this crisis. With the limited number of dedicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 4 publications
(5 reference statements)
0
16
0
1
Order By: Relevance
“…Coagulopathy in COVID-19 results from endothelial damage, complement activation, and cytokine release and can cause acute limb ischemia (ALI) by worsening a chronic vasculopathy or causing peripheral embolization from newly formed thrombus 54 , 55 , 56 . Numerous studies have demonstrated the increased incidence of ALI during the pandemic and the devastating associated outcomes 56 , 57 , 58 , 59 , 60 . Multiple studies reported an increased ALI incidence during the pandemic in Lombardy, Italy, one of the hardest COVID-19 struck regions in the world; 305 referred vascular surgery patients at the peak of the pandemic were analyzed, and although only 21% were found to have COVID-19, two-thirds of ALI cases occurred in COVID-19 positive patients 56 , 59 .…”
Section: Clinical Impact Of Covid-19mentioning
confidence: 99%
“…Coagulopathy in COVID-19 results from endothelial damage, complement activation, and cytokine release and can cause acute limb ischemia (ALI) by worsening a chronic vasculopathy or causing peripheral embolization from newly formed thrombus 54 , 55 , 56 . Numerous studies have demonstrated the increased incidence of ALI during the pandemic and the devastating associated outcomes 56 , 57 , 58 , 59 , 60 . Multiple studies reported an increased ALI incidence during the pandemic in Lombardy, Italy, one of the hardest COVID-19 struck regions in the world; 305 referred vascular surgery patients at the peak of the pandemic were analyzed, and although only 21% were found to have COVID-19, two-thirds of ALI cases occurred in COVID-19 positive patients 56 , 59 .…”
Section: Clinical Impact Of Covid-19mentioning
confidence: 99%
“… 23 Several articles had also reported an increase in major amputation rates during the COVID-19 pandemic. 26 , 27 , 37 , 38 This occurrence could be a result of delayed case presentation as discussed earlier, or can be due to a change in surgical practice. Limb salvage can be a resource-intensive process involving long hospitalizations coupled with multiple re-interventions.…”
Section: Resultsmentioning
confidence: 95%
“…A total of 19 articles had reported changes in the conduct of emergency and elective VS cases in respective institutions. 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 In summary, all articles reported continuation of emergency VS cases such as ruptured AAAs, and deferment of non-urgent elective VS cases such as revascularization for claudicants and varicose veins. There was some inter-institutional variation between the type of VS cases that proceeded or were deferred.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations